Neurotoxidade Neonatal do Metilmalonato é suficiente para iniciar déficit de memória em camundongos: envolvimento de marcadores inflamatórios e apoptóticos - Gabbi, Patricia (2014)
The methylmalonic acidemia is an inborn error of metabolism (IEM) characterized by methylmalonic acid (MMA) accumulation in body fluids and tissues, causing neurological dysfunction, mitochondrial failure, oxidative stress and neuroinflammation. Although neurological evidence demonstrate that infection and/or inflammation mediators facilitate metabolic crises in patients, the involvement of neuroinflammatory processes in the neuropathology of this organic acidemia is not yet established. In this experimental study, a single intracerebroventricular dose of MMA (MMA 2.5μmol /g, 12 hs after birth; at dose that raise its concentration in blood and in the brain from affected) was administered to mice pups at postnatal day 0 (P0) to induce an acute, transient rise of MMA levels in the central nervous system (CNS). In the following days (21st 33th or 40th 52th ) animal behavior was assessed in the radial maze test and elevated plus maze. It was measured tumor necrosis factor-alpha (TNF-α), DCFH, Ache activity and caspase levels in the cerebral cortex, striatum and hipoccampus from mice with 21 e 40 days of life. Behavioral tests showed that animals injected with MMA have a reduction in the working memory test, but no in the reference test. The animals did not exhibit anxiety-like behaviors. Furthermore, MMA increased levels of TNF-α, AchE activity and activation of caspases 1, 3 and 8 in the cerebral cortex, hippocampus and striatum of mice with 21 and 40 days of life. The overall results indicate that a simple administration of MMA increased pro-inflammatory markers in the structure studied, increased apoptotic markers, and coincide with the behavioral changes found in young mice. This leads to speculate that, through mechanisms not yet elucidated, the transient metabolic insult with MMA may cause a neuroinflammatory processes during critical periods of development, contributing to the progression of cognitive impairment in patients with methylmalonic acidemia.